Melting stones - Pierce, Tamora; Kelly, Grace (Syracuse, NY : Full Cast Audio, 2007)
Evvy has accompanied her guardian, Rosethorn, on a mission to study a mysterious plant die-off. Preventing a natural disaster may cost Evvy her life....
Unabridged.
Compact disc.
Read by Grace Kelly and the Full Cast family.
Keywords: Magic; Children's audiobooks; Fantasy fiction; Fantasy fiction; Audiobooks